2021
DOI: 10.5708/ejmh.16.2021.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Family Characteristics as Determinants of Mental Health in Adolescents

Abstract: The family environment is considered to be a micro-ecological system with numerous risk and protective factors for mental health. The goal of this research was to determine how different functional and/or structural family characteristics affect some indicators of mental health in adolescents. A number of 1,239 adolescents (ages 15–19) participated in the research. General Data Questionnaire, Family Life Satisfaction Scale, Family Communication Scale, Positive Mental Health Scale, Anxiety, Depression and Stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Echoing previous research, family, friend, school and self-satisfaction significantly negatively predicted psychological distress and problem behaviours (Bae, 2015;Jovаnovic & Jerkovic, 2011;Maglica et al, 2021;Yao et al, 2017). Compared with other forms of life satisfaction, school satisfaction had a stronger effect on problem behaviours.…”
Section: Association Of Life Satisfaction With Psychological Distress...mentioning
confidence: 63%
See 1 more Smart Citation
“…Echoing previous research, family, friend, school and self-satisfaction significantly negatively predicted psychological distress and problem behaviours (Bae, 2015;Jovаnovic & Jerkovic, 2011;Maglica et al, 2021;Yao et al, 2017). Compared with other forms of life satisfaction, school satisfaction had a stronger effect on problem behaviours.…”
Section: Association Of Life Satisfaction With Psychological Distress...mentioning
confidence: 63%
“…Previous research showed that satisfaction in different domains of life was related to adolescents' internalizing and externalizing mental health problems. Low levels of family satisfaction were associated with internalizing mental health problems (Maglica et al, 2021) and suicidal behaviours (Pillay & Wassenaar, 1997). High levels of school satisfaction were associated with higher levels of subjective well‐being, lower levels of emotional distress and greater academic achievement (Jovаnovic & Jerkovic, 2011); lower levels of school satisfaction were associated with more consumption of tobacco or alcohol (Morioka et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the evolving emphasis on positive mental health has led to a more nuanced understanding of its role in promoting mental well-being and preventing mental disorders, highlighting the potential for positive communication patterns within families to contribute to overall mental health (MaggiStefania et al, 2013). Additionally, barriers to accessing perinatal mental health services have been found to interact with family and individual level factors, influencing maternal mental health outcomes (Maglica et al, 2021). The compounding challenges faced by disadvantaged communities in accessing mental health resources point to the need for enhanced support and opportunities for promoting wellbeing within families affected by mental health needs (Sanchez et al, 2020).…”
Section: Impacts On Mental Healthmentioning
confidence: 99%